2021
DOI: 10.1001/jama.2021.3414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Poloxamer 188 vs Placebo on Painful Vaso-Occlusive Episodes in Children and Adults With Sickle Cell Disease

Abstract: IMPORTANCEAlthough effective agents are available to prevent painful vaso-occlusive episodes of sickle cell disease (SCD), there are no disease-modifying therapies for ongoing painful vaso-occlusive episodes; treatment remains supportive. A previous phase 3 trial of poloxamer 188 reported shortened duration of painful vaso-occlusive episodes in SCD, particularly in children and participants treated with hydroxyurea.OBJECTIVE To reassess the efficacy of poloxamer 188 for vaso-occlusive episodes.DESIGN, SETTING,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…Since the discovery of SCD in modern history in 1910, there are only four FDA approved drugs for the prevention of pain in SCD, three of which received approval only in the last 5 years [ [10] , [11] , [12] ]. Currently, there is no FDA approved drug for the treatment of acute VOC, although a few drugs have been tested in clinical trials and without successful results [ [13] , [14] , [15] ]. The conduct of clinical trials in SCD has been challenging in this minority population for an otherwise complicated clinical outcome of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of SCD in modern history in 1910, there are only four FDA approved drugs for the prevention of pain in SCD, three of which received approval only in the last 5 years [ [10] , [11] , [12] ]. Currently, there is no FDA approved drug for the treatment of acute VOC, although a few drugs have been tested in clinical trials and without successful results [ [13] , [14] , [15] ]. The conduct of clinical trials in SCD has been challenging in this minority population for an otherwise complicated clinical outcome of pain.…”
Section: Discussionmentioning
confidence: 99%
“…In the last several years, there has been an exponential growth in the number of clinical trials in SCD, made possible due to close partnerships between the pharmaceutical industry and academia [ 16 ]. However, the design of the clinical trial in SCD is critically important for the successful outcome; for example, the poloxamer 188 trial for VOC showed significant and positive findings initially, but unfortunately failed to achieve approval because of negative results in the final phase 3 trial [ 15 , 17 ]. This is partly because the clinical endpoints were different between the different phases of the trials [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial of children and adults with sickle cell disease, P188 of intravenous therapy (100 mg/kg) for one hour triggered adverse events including abdominal distension, hepatobiliary disorders, hyperbilirubinemia; the above adverse events were resolved in 30 days [ 29 ]. In addition, a recent pharmacological study reported that treatment of P188 alone induced the expression of IL-6 [ 30 ], suggesting P188 is potential immune stimulator. Above studies support the mechanism, application, and safety dose of P188 as potential adjuvant in formulation of subunit vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…At present, we conclude that ticagrelor is not effective for the prevention of vaso-occlusive crises in pediatric patients with the SCD genetic traits HbSS and HbS/β 0 . Unfortunately, the negative result of the HESTIA3 trial of ticagrelor joins a list of negative results for other investigational agents in SCD, including senicapoc, 38 prasugrel, 23 regadenoson, 39 sevuparin, 40 poloxamer 188, 41 olinciguat, 42 and rivipansel. 43 There continues to be a significant unmet need for prevention and treatment of vaso-occlusive crises in SCD.…”
Section: Discussionmentioning
confidence: 99%